Ultimate space telescope [videorecording (DVD)] - Randall, Terri; Sechler, Craig; Steward, Alphonso; Straughn, Amber; Menzel, Mike; Tay, CheeWei (PBS, 2022)
"How did NASA engineers build and launch the most ambitious telescope of all time? Follow the dramatic story of the James Webb Space Telescope -- the most complex machine ever launched into space. If it works, scientists believe that this new eye on the universe will peer deeper back in time and space than ever before to the birth of galaxies, and may even be able to "sniff" the atmospheres of exoplanets as we search for signs of life beyond Earth. But getting it to work is no easy task. The telescope is far bigger than its predecessor, the famous Hubble Space Telescope, and it needs to make its observations a million miles away from Earth -- so there will be no chance to go out and fix it. That means there's no room for error; the most ambitious telescope ever built needs to work perfectly. Meet the engineers making it happen and join them on their high stakes journey to uncover new secrets of the universe."--Container.